Microbial and Biogeochemical Dynamics in Glacier Forefields Are Sensitive to Century-Scale Climate and Anthropogenic Change - Bradley, James A.; Anesio, Alexandre M.; Arndt, Sandra (Frontiers in Earth Science, 2017)
The recent retreat of glaciers and ice sheets as a result of global warming exposes forefield soils that are rapidly colonised by microbes. These ecosystems are dominant in high-latitude carbon and nutrient cycles as microbial activity drives biogeochemical transformations within these newly exposed soils. Despite this, little is known about the response of these emerging ecosystems and associated biogeochemical cycles to projected changes in environmental factors due to human impacts. Here, we applied the model SHIMMER to quantitatively explore the sensitivity of biogeochemical dynamics in the forefield of Midtre Lovénbreen, Svalbard, to future changes in climate and anthropogenic forcings including soil temperature, snow cover, and nutrient and organic substrate deposition. Model results indicated that the rapid warming of the Arctic, as well as an increased deposition of organic carbon and nutrients, may impact primary microbial colonisers in Arctic soils. Warming and increased snow-free conditions resulted in enhanced bacterial production and an accumulation of biomass that was sustained throughout 200 years of soil development. Nitrogen deposition stimulated growth during the first 50 years of soil development following exposure. Increased deposition of organic carbon sustained higher rates of bacterial production and heterotrophic respiration leading to decreases in net ecosystem production and thus net CO2 efflux from soils. Pioneer microbial communities were particularly susceptible to future changes. All future climate simulations encouraged a switch from allochthonously-dominated young soils (<40 years) to microbially-dominated older soils, due to enhanced heterotrophic degradation of organic matter. Critically, this drove remineralisation and increased nutrient availability. Overall, we show that human activity, especially the burning of fossil fuels and the enhanced deposition of nitrogen and organic carbon, has the potential to considerably affect the biogeochemical development of recently exposed Arctic soils in the present day and for centuries into the future. These effects must be acknowledged when attempting to make accurate predictions of the future fate of Arctic soils that are exposed over large expanses of presently ice-covered regions.